MANAJEMEN SIARAN MUSIK PADA MUSIC DIRECTOR RADIO FRESH 94,3 FM PEKANBARU DALAM MEMPERTAHANKAN EKSISTENSI - Novriska, Ruth Dikta; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Radio is an institution electronic media beside television which still exist from competition with other media type, such as competition or promotion of product. The determination of the music genre as a characteristic of a radio because music is the lifeblood of a radio, then in order to maintain the existence and survival of a companies, it should takes good management regulation to reach the goals of the enterprise agencies. Fresh Radio 94.3 FM is one ofradio with new management and different style to the other radio. Fresh Radio 94.3 FM properly managed by Music Director, , so that the songs are set according to the segmentation, in accordance with the atmosphere, where it captures the audience radio class A and B, the middle and upper.This research used qualitative method. The technique of collection data in this study used interviews. The location of this research was in Radio Fresh 94, 3 Fm, Pekanbaru. The writer had 3 informant for this research, they are the Music Director, Program Director and Station Manager of Radio Fresh 94, 3 FmPekanbaru. The researcher took an informantsby using purposive sampling technique. The researcher used interactive and analytical methods for checking the validity of the data, then, researchers used data triangulation technique.The result of this reseacrh shows that planning 94.3 Fm Radio Fresh Pekanbaru include determining segmentation, then create music programs, and determine the genre of music as a characteristic of the radio itself. Organizing conducted regulate processes including scheduling program that is formed with the aim of creating an image format radio station Fresh 94, 3 Fm Pekanbaru. Directing the work done in coordination between the Program Director and Music Director in making a music program, but in fact frequent breakdowns caused their employees (staff) incorrectly translates the command from the leadership. Radio Fresh 94,3Fm Pekanbaru have two kind of evaluation namely the evaluation of the monitoring is to evaluate existing programs, and evaluation of impact, how the results and impact of programs already established.Keyword : Radio, Management, Music Director